2012
DOI: 10.1111/j.2044-8341.2012.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Learning to live with OCD is a little mantra I often repeat’: Understanding the lived experience of obsessive‐compulsive disorder (OCD) in the contemporary therapeutic context

Abstract: Having OCD as a condition meant that individuals experienced a sense of overwhelming personal failure matched against age appropriate life cycle goals. This crisis of the self was bolstered by public and self-stigma about the condition. While clinical diagnosis and therapeutic interventions were significant, participants reported dialectical tensions experienced with OCD, pointing to the complexity of psychological functioning in the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
4
24
2
Order By: Relevance
“…Given our limited level of knowledge on seeking help for OCD, there is a particular need for in‐depth studies. We found five qualitative studies with a bearing on this area: one on anticipated stigma and actual experience of stigma (Stengler‐Wenzke, Beck, Holzinger, & Angermeyer, ), one on pathways to psychiatric care (Stengler‐Wenzke & Angermeyer, ), and three on the lived experience of OCD, including the experience of stigma (Fennell & Liberato, ; Harrington, ; Murphy & Perera‐Delcourt, ). However, we found no qualitative studies specifically examining the barriers and enablers in seeking help for OCD.…”
Section: Introductionmentioning
confidence: 99%
“…Given our limited level of knowledge on seeking help for OCD, there is a particular need for in‐depth studies. We found five qualitative studies with a bearing on this area: one on anticipated stigma and actual experience of stigma (Stengler‐Wenzke, Beck, Holzinger, & Angermeyer, ), one on pathways to psychiatric care (Stengler‐Wenzke & Angermeyer, ), and three on the lived experience of OCD, including the experience of stigma (Fennell & Liberato, ; Harrington, ; Murphy & Perera‐Delcourt, ). However, we found no qualitative studies specifically examining the barriers and enablers in seeking help for OCD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarities with other qualitative studies are striking. For example, this study's theme of ‘The battle of living with OCD’ maps onto Murphy and Perera‐Delcourt's () theme of ‘Failing at life’. Furthermore, stigma and difference as described in the current study are omnipresent across qualitative studies on OCD, for example ‘Wanting to be normal and fit in’ (Murphy & Perera‐Delcourt, ); ‘Feeling different’, ‘Personal shame’, and ‘Stigmatisation’ (Brooks, ), ‘OCD is a ‘joke’ condition – not recognised as serious’ (Fennell & Liberato, ).…”
Section: Discussionmentioning
confidence: 93%
“…They identified four overarching themes, which included participants ‘interrogating their feelings to achieve a sense of certainty’; ‘ceaselessly and carefully’ seeking to be reassured in a range of ways; experiencing a ‘reluctance to seek reassurance’; and finally, experiencing ‘interpersonal concern’ due to feelings of embarrassment, guilt, gratitude and compensation. An interpretative phenomenological analysis involving adults with an OCD diagnosis (Murphy & Perera‐Delcourt, ) identified that people ‘wanted to be normal and fit in’; felt that they were ‘failing at life’; and wanted to ‘find the roots’ of their difficulties. Furthermore, an auto‐ethnographic study of an adult highlighted how the fear of stigmatisation, a strong sense of personal shame, and feeling ‘different’ functioned to keep obsessions private (Brooks, ).…”
Section: Introductionmentioning
confidence: 99%
“…It may be important to consider another subjective facet in the definition of recovery. Every mental disorder intrinsically entails a component of self-stigma, but this is particularly true for OCD, where diminished self-esteem is related to the perceived ego-dystonicity of the symptoms and the insight harbored by a high proportion of patients ( Catapano et al, 2001 ; Murphy and Perera-Delcourt 2014 ). Moreover, it is questionable how a term that derives from the Inquisition Era, such as “obsessive-compulsive disorder” referring to a lucid demonic possession ( Robbins 1959 ), is still included in the current nosography.…”
Section: Recovery: Application Of the Concept To Ocdmentioning
confidence: 99%